Green chemistry route of biosynthesized copper oxide nanoparticles using Psidium guajava leaf extract and their antibacterial activity and effective removal of industrial dyes. Issue 2 (April 2021) - Sathiyavimal, Selvam; Vasantharaj, Seerangaraj; Veeramani, Veerasamy; Saravanan, Mythili; Rajalakshmi, Govindaraju; Kaliannan, Thamaraiselvi; Al-Misned, Fahad A.; Pugazhendhi, Arivalagan
Abstract: In current scenario, the eco-friendly and non-toxically biosynthesis of cupric oxide is also known as copper oxide nanoparticles (CuO NPs) by using Psidium guajava ( P . guajava ) leaf extract to potential valuable in the wastewater treatment as well as biomedical application. To this unique technology for biosynthesis of CuO NPs was utilizing phytocompounds from aqueous plant extract during the reaction mixture, which possessed natural bio-compounds to act as stabilizing, capping and reducing agent of CuO NPs. In the present investigation, biosynthesized CuO NPs and their physicochemical properties were analyzed by using ultraviolet–visible spectroscopy (UV) was initially to be identified formation of CuO NPs the characteristic peak at 265 nm. Furthermore, Fourier-transform infrared spectroscopy (FTIR) analysis to be confirmed functional groups of biosynthesized CuO NPs the absorption range of 624–870 cm ‐1 and the X-ray diffraction (XRD) study was performed to determine the monoclinic crystalline structure of the CuO NPs. Field emission scanning electron microscopy (FE-SEM) and High-resolution transmission electron microscopy (HR-TEM) with Selected area electron diffraction (SAED) pattern to analyzed for the identification of particles surface morphology showed oval and platelets and sizes range from 40 to 150 nm. Energy-dispersive X-ray spectroscopy (EDS) spectrum to confirmed quantitative evaluation of Cu and O elements in the prepared samples. Dynamic light scattering (DLS) to determined average particles size of CuO NPs 153 nm. The prepared CuO NPs was observed highest anti-bactericidal activity against Gram negative (G−) bacteria of Escherichia coli, Pseudomonas aeruginosa and then compared to Gram positive (G+) bacteria of Streptococcus pneumoniae, Staphylococcus epidermidis to be confirmed using agar well diffusion, and their NPs interaction on the bacterial membrane to be confirmed by confocal laser scanning microscopic (CLSM) to visualized live/dead bacterial cells. In addition to be performed the biosynthesized CuO NPs has potential industrial dye removal of congo red (CR) and methylene blue (MB) under the sunlight irradiation. Graphical Abstract: ga1 Highlights: Eco-friendly and low cost effectively biosynthesized of CuONPs using Psidium guajava leaf extract. Bandgap energy disclosed formation of monoclinic structure of the biosynthesized CuONPs. Biosynthesized CuONPs have potential antibacterial activity against both Gram-positive and Gram-negative bacteria. Non-toxic synthesized CuONPs were exhibited good photocatalytic degradation for congo red (CR) and methylene blue (MB).